Automated Close-Loop System for Three-Dimensional Characterization of Spatiotemporal Optical Vortex - Chen, Jian; Lu, Keyin; Cao, Qian; Wan, Chenhao; Hu, Haifeng; Zhan, Qiwen (Frontiers in Physics, 2021)
Recent rapid advances in spatiotemporal optical pulses demand accurate characterization of the spatiotemporal structure of the produced light fields. We report an automated close loop characterization system that is capable of reconstructing the three-dimensional intensity and phase structures of spatiotemporal wavepacket illustrated by characterizing spatiotemporal optical vortex in the spatiotemporal domain. The characterization technique is based on interfering a much shorter probe pulse with different slices of the object wavepacket along the temporal axis. A close loop control program is developed to realize full automation of the data collection and reconstruction process. Experimental results of the intensity and phase distributions show that the designed close loop system is efficient in quantitatively characterizing the generated spatiotemporal optical vortex. Such a linear characterization system can also be extended to measure many other kinds of spatiotemporal wavepacket and may find broad applications in spatiotemporal wavepackets studies.